Synthesis and Spectroanalytical Studies of a New Azodye Derived From 2-Amino-6-ethoxybenzothiazole and 4Chloro-3,5-dimethylphenol and its Complexes With Fe (III) Ion - Ali, Asaad A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study involves the synthesis of new azodye, derived from 2-Amino-6ethoxybenzothiazole and 4-Chloro-3,5-dimethylphenol . The characterization of dye has been described by C.H.N. The TG , IR and Visible. spectroscopic techniques .The acid-base properties were studied at different pH values . The ionization and protonation constants of dye were determined. Solvents effects were also studied at different solvents polarities . The optimum conditions of this formation of complex with Fe(III) were investigated . The analytical applications of this azodye , were studied like; using it as acid-base indicator , and for the determination of nitrite ions